THE EFFECT OF RISK MANAGEMENT ON ORGANIZATIONAL PERFORMANCE - Samsul hadi (IJED: International Journal of Economy Development Research, 2022)
AbstractPension Fund as a legal entity that manages wealth and runs a pension program that promises pension benefits to maintain sustainable income for its participants, in the retirement period, is very vulnerable to risk. In the context of Pension Fund management, the risk faced is the problem of insufficient funds which in turn can interfere with the fulfillment of the Pension Fund's obligations to pay participants' rights to receive pension benefits. Implementing risk management in the Pension Fund, can assist the Pension Fund Management in improving organizational performance in the Pension Fund This study aims to examine the effect of the application of risk management on organizational performance. This study measures the extent to which the application of risk management helps carry out important managerial functions so as to improve organizational performance. The results show that: the application of risk management has a significant effect on organizational performance at the Employer Pension Fund which organizes the Defined Benefit Pension Program throughout West Java-Banten This research was conducted on a Pension Fund with a Defined Benefit Pension Program in the West Java-Banten region, so the results cannot be generalized to other contexts. The findings of this study reinforce the importance of implementing risk management in improving organizational performance. This study contributes to the very little literature review that examines the significant relationship between the implementation of risk management and organizational performance.